2011
DOI: 10.1104/pp.111.183723
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Purple Acid Phosphatase AtPAP10 Is Predominantly Associated with the Root Surface and Plays an Important Role in Plant Tolerance to Phosphate Limitation    

Abstract: Induction of secreted acid phosphatase (APase) is a universal response of higher plants to phosphate (Pi) limitation. These enzymes are thought to scavenge Pi from organophosphate compounds in the rhizosphere and thus to increase Pi availability to plants when Pi is deficient. The tight association of secreted APase with the root surface may make plants more efficient in the utilization of soil Pi around root tissues, which is present in organophosphate forms. To date, however, no systematic molecular, biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
212
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(223 citation statements)
references
References 51 publications
8
212
0
Order By: Relevance
“…A negative correlation between the level of Pi in medium and APase activity has been reported in many plants (e.g., del Pozo et al 1999;Haran et al 2000;Liu et al 2005;Veljanovski et al 2006;Morcuende et al 2007;Muller et al 2007). It has also been shown that overexpressions of secreted PAPs with phytase activity improve plant biomass and Pi accumulation (Xiao et al 2006;Ma et al 2009;Wang et al 2009Wang et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between the level of Pi in medium and APase activity has been reported in many plants (e.g., del Pozo et al 1999;Haran et al 2000;Liu et al 2005;Veljanovski et al 2006;Morcuende et al 2007;Muller et al 2007). It has also been shown that overexpressions of secreted PAPs with phytase activity improve plant biomass and Pi accumulation (Xiao et al 2006;Ma et al 2009;Wang et al 2009Wang et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative Analyses of Anthocyanin, Cellular Pi, and Total P Anthocyanin, cellular Pi, and total P were quantified as described by Wang et al (2011).…”
Section: Mutant Isolationmentioning
confidence: 99%
“…Intracellular and root surface-associated APase activities were quantified as described by Wang et al (2011).…”
Section: Quantitative Analysis Of Apase Activitymentioning
confidence: 99%
“…Pi uptake mechanisms are enhanced at the root/soil interface, particularly through the stimulation of Pi transport activity (Mudge et al, 2002;Shin et al, 2004;Nussaume et al, 2011; Ayadi et al, 2015). In parallel, mobilization of Pi sources from the soil is facilitated by the secretion of acid phosphatases and acidification of the soil surrounding roots (Raghothama, 1999;Plaxton and Tran, 2011;Wang et al, 2011;Zhang et al, 2014; Balzergue et al, 2017).Pi stored within cells also represents an important nutrient source, and plants demonstrate an extraordinary capacity to mobilize these stocks during starvation (Ticconi and Abel, 2004). Vacuoles are the major storage compartment for Pi in the cell (storing about 80% of the total cellular Pi) in nonlimiting conditions (Bieleski, 1983;Poirier and Bucher, 2002).…”
mentioning
confidence: 99%
“…Pi uptake mechanisms are enhanced at the root/soil interface, particularly through the stimulation of Pi transport activity (Mudge et al, 2002;Shin et al, 2004;Nussaume et al, 2011; Ayadi et al, 2015). In parallel, mobilization of Pi sources from the soil is facilitated by the secretion of acid phosphatases and acidification of the soil surrounding roots (Raghothama, 1999;Plaxton and Tran, 2011;Wang et al, 2011;Zhang et al, 2014; Balzergue et al, 2017).…”
mentioning
confidence: 99%